An economic assessment of micro-scale use of renewable energy sources : two case studies - Palomino Ramirez, Horacio (2015)
During recent times, renewable energy technologies have shown a relative fast growth in the global energy investment, global energy capacity and their integration within multiple sectors, particularly in the electricity sector. Renewable energy technologies have also experienced notorious declining costs on their manufacturing production. Nevertheless, while this growth is widely acknowledged, the share of renewables with respect total energy production has been moderate. Technological advancements in renewable energy have demonstrated the potential of renewables in energy generation and also that renewables can provide direct and indirect advantages over their counterparts. This thesis investigates two specific cases in which the renewable energy technologies of wind power and solar photovoltaics could be widely employed on micro-scale energy generation. The study’s objective is to gain deeper understanding if such applications of these forms of renewables are, foremost, economically viable at micro-scale or individual level. The research was carried out by means of quantitative case study in which theoretical analysis, mathematical modelling, and experimental empirical measurements were employed in order to make a thoroughly analysis and cross validate the study’s results and findings. The results from this investigation suggest that the employment of wind and solar renewables at micro-scale are economically profitable if favourable weather conditions exist at the location. If there are no favourable weather conditions, then these renewables will be economically viable if external costs such as transportation, installation and maintenance are absorbed by the owner. Moreover, this thesis suggest that better incentives, besides economically, are needed such as communication strategies and wider distribution channels in order to promote the use of renewables to the general public. This thesis also suggests that by engaging in renewable energy generation by first-hand experience encourages a sense of responsibility and the importance of saving energy which would be difficult to attain otherwise.